Analisis Kinerja Keuangan Pada Bank Sinarmas Dengan Menggunakan Common Size - Dwi Budi Srisulistiowati; Rani Suryani; Sri Rejeki (UNIVED Press, 2023)
The purpose of the study was to determine the composition of assets, liabilities and total income in the financial statements of Bank Sinarmas using the Common Size method. The type of research in this research is quantitative research. The data used is secondary data, namely financial statements in the form of balance sheets and income statements for 2019-2021. The results showed that the balance sheet, especially assets, increased, but on the cash side it decreased. Liabilities, especially liabilities, experienced stability from 2019-2021. Equities are also experiencing stability. This shows that the bank's financial development is stable, where the proportion of liabilities is greater than the proportion of equity. While on the income statement, seen from other operating income experiencing instability and profit for the year increased in 2019-2021, this shows that the performance of Bank Sinarmas in 2019-2021 was good because the company was able to maintain its net profit in the following year.